Electromagnetic performance of switched flux PM machines with two separate stators. Issue 2 (7th March 2016) - Awah, Chukwuemeka Chijioke; Zhu, Z.Q.; Wu, Zhongze; Wu, Di; Ge, Xiao
Abstract : Purpose: – The purpose of this paper is to propose a novel type of switched flux PM machines with two separate stators. Design/methodology/approach: – 2D-FEA is employed to analyze the electromagnetic performance of the proposed machines. Moreover, the results are validated by experiments. Findings: – The proposed machine has higher torque density, less unbalanced magnetic force on the modulating steel piece and uses less PM volume. Originality/value: – The proposed machine is a low-cost novel topology with different rotor pole combinations.